Forest Ecohydrology: From Theory to Practice - Wang, Yanhui; Feger, Karl-Heinz; Zhang, Lulu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Forests are inherently linked to water resources and water-related ecosystem services. Therefore, an integrated forest-water management system is urgently required to ensure a balanced supply of hydrological and other ecosystem services from forests to meet the fast-increasing societal demands for them. This means that water aspects must be integrated into traditional forest management focusing mainly on timber production, and based on the knowledge and the latest scientific results of forest ecohydrology. Unfortunately, there are a lot of gaps in our knowledge of forest ecohydrology. This reprint presents relevant new results from scientific research on forest ecohydrology, related to the drought tolerance mechanism, hydrological properties of soil and litter layers, variation in solar radiation within stands, snowpack isotopic composition in open and forested areas, canopy transpiration and response to the main influencing factors, and the water balance components of typical forests at different regions with various climates. This knowledge can contribute to the theoretical development of forest ecohydrology and the innovative practice of integrated forest-water management to enhance the balanced supply of hydrological and other ecosystem services from forests.